2021
DOI: 10.52037/eads.2021.0004
|View full text |Cite
|
Sign up to set email alerts
|

Color stability and surface roughness of resin based direct and indirect restorative materials

Abstract: Purpose: This study investigated discoloration and surface roughness (Ra) of resin-based computer aided design (CAD)/computer aided manufacturing (CAM) blocks and direct and indirect resin composites after staining with coffee. Materials & Methods: Using a Teflon mold, 60 disc shaped specimens (8×2 mm2) were fabricated from direct (Estelite Asteria and GrandioSO) and indirect (Gradia Plus) resin composites, and 30 resin CAD/CAM specimens (12×14×2 mm3) were prepared from resin composite CAD/CAM blocks (Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…Therefore, the first null hypothesis that the color stability of composite block, nanohybrid, and microhybrid resin composites would not be different was rejected. The result is in agreement with previous studies, which have concluded that the indirect composite blocks had lower color change values than direct resin composites (3,19).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, the first null hypothesis that the color stability of composite block, nanohybrid, and microhybrid resin composites would not be different was rejected. The result is in agreement with previous studies, which have concluded that the indirect composite blocks had lower color change values than direct resin composites (3,19).…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with previous studies in which the repolishing provided a significant improvement in the discoloration of resin composites (5,16,18), ceramics, and resin-based composite blocks (9). In a previous study, repolishing did not affect the color change of the composite block Cerasmart, and this was attributed to a low discoloration degree (19). Nonetheless, internal discolorations may not be completely removed by repolishing (9,30).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Depending on the developments in computeraided design and manufacturing (CAD / CAM) technology, resin-containing CAD / CAM blocks have been introduced to the market. While these materials, which are used by indirect methods, are advantageous because of the advantageous properties of ceramics, such as durability and color stability, and superior physical properties of composite resins, such as improved bending and low abrasiveness (3), the fact that composite resin formulations have a much higher potential to be stained than ceramic due to temperature changes in the oral environment and coloring beverages, can also be seen as a disadvantage (4).…”
Section: Introductionmentioning
confidence: 99%